Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Kerja, dan Budaya Organisasi Terhadap Kinerja Karyawan di Lembaga Perkreditan Desa (LPD) Desa Pakraman Padangsambian - Komang Dewi Puspita; Ni Wayan Mujiati (Universitas Batanghari Jambi, 2023)
LPD Desa Pakraman Padangsambian is one of the financial institutions owned by Desa Pakraman in the West of Denpasar city area. LPD Desa Pakraman Padangsambian also offers a variety of financial products and services to the community. One of the services offered by the Padangsambian Pakraman Village LPD is providing credit, which is much favored by the community. This study aims to examine and explain the influence of transformational leadership style on employee performance, the effect of work motivation on employee performance, the influence of organizational culture on employee performance at LPD Desa Pakraman Padangsambian. The sample in this study are 34 respondents using saturated sampling method, namely the sampling technique when all members of the population are used as samples. Data collection was carried out through distributing questionnaires. The collected data were analyzed using the classical assumption test, multiple linear regression analysis techniques. The results of this study show that transformational leadership style has a significant positive effect on employee performance, work motivation has a significant positive effect on employee performance, organizational culture has a significant positive effect on employee performance at LPD Desa Pakraman Padangsambian. The advice that can be given is that it is hoped that the head of the LPD Desa Pakraman Padangsambian can raise employee morale by helping employees when employees experience problems and can also provide good examples for employees so that employees are able to make superiors as their guide in work, the head of the LPD Desa Pakraman Padangsambian is expected can mediate between employees who have disagreements so that mutual trust will be created between employees so this can improve employee performance, and the head of the LPD Desa Pakraman Padangsambian is expected to be able to provide structured work so that employees are able to complete their work on time